Best seller [videorecording (DVD)] - Woods, James, 1947-; Dennehy, Brian; Tennant, Victoria, 1950- (Olive Films, 2015)
Set in 1972 in Los Angeles, a professional assassin decided to get revenge for being let go from the corporate empire he helped build by writing a tell all book. The question is who will still remain standing after the assassin's former employer kidnaps the writer's daughter and a confrontation ensues.